Penerapan Mekanisme Penyelesaian Sengketa Alternatif (Alternative Dispute Resolution) Dalam Electronic Commerce Sebagai Salah Satu Upaya Perlindungan Hukum - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
ABSTRACT An increace of information technology in commercial activities, is not only giving many advantages for bossiness actors, but also many problems, such as: failures to delivery, errors in order taking and failures to pay. In connection with the above problems, there are a number of questions to be answered in this research, namely: (1) what are the factors that motivate parties to choose the Alternative Dispute Resolution (ADR)? (2) how the ADR in electronic commerce transaction dispute is formally applied?